Ta‘Līmu Mahārati Al-Kalām Al-Qā’imi ‘Ala Al-Mashrū‘ Bi-Istikhdāmi Muḥtawā Al-Fīdiyū Fī Al-Lughah Al-‘Arabiyyah - Ritma Eka Solikhah; Sutaman Sutaman; Shofil Fikri (STIQ Amuntai, 2025)
Arabic speaking skills are crucial for communication, but are often hampered by a lack of practice, motivation and confidence, requiring innovative project-based and technology-based strategies. The aim of this research is: 1) to describe the process of implementing project-based speaking skills learning at MAN Insan Cendekia Pesuruan; 2) explaining the impact of implementing project-based speaking skills learning at MAN Insan Cendekia Pesuruan. This research used a qualitative approach with a case study. Data were collected through observation, interviews and documentation and analysed using the Miles and Huberman models. The results of the research show that: 1) Project-based speaking skills learning with video content at MAN Insan Cendekia Pasuruan was carried out through careful planning and systematic steps, starting from group formation, theme selection, script writing, practice, recording, and screening. The themes raised were relevant to everyday life, thus supporting contextual and communicative learning, these themes include sports, seeking medical treatment, shopping, visiting sick people, and other themes.; 2) The results of the implementation showed an improvement in students' linguistic skills, such as vocabulary, pronunciation, and sentence structure, as well as non-linguistic developments in the form of confidence, motivation, and cooperation. The use of video media also provided a space for creative expression that was familiar to the students' digital world. Thus, the project-based speaking skills learning using video content model was effective in improving speaking skills while building social skills and 21st-century competencies.